Combined assessment of carotid intima–media thickness and epicardial fat thickness for cardiovascular risk stratification in asymptomatic South Indian adults - Ramesh Sankaran; Dolly Agarwal; Rahul Mittal; Shankar Srinivasan; Nagendra Boopathy Senguttuvan; Alex Karev; Sadhanandham Shanmugasundaram; Balasubramaniyan Jayanthi Venkata; Vinod Kumar Balakrishnan; Preetam Krishnamurthy; Sadagopan Thanikachalam; Murthy Jayanthi Satyanarayana (Frontiers in Cardiovascular Medicine, 2026)
Background Carotid intima-media thickness (cIMT) and epicardial fat thickness (EFT) are non-invasive imaging markers associated with cardiovascular risk. This study evaluated the associations between cIMT, EFT, individual cardiovascular risk factors, cumulative cardiovascular risk-factor burden in asymptomatic adults undergoing routine cardiovascular health assessment. Methods A cross-sectional study was conducted in 925 asymptomatic adults aged ≥18 years undergoing routine cardiovascular health evaluations. Participants were classified into a control group without cardiovascular risk factors ( n = 179) and a study group with one or more cardiovascular risk factors ( n = 746). Carotid intima-media thickness was measured using carotid ultrasonography, and epicardial fat thickness was assessed by transthoracic echocardiography. Associations between imaging measurements, cardiovascular risk factors, cumulative cardiovascular risk-factor burden, were evaluated using descriptive and comparative statistical analyses. Results Participants with one or more cardiovascular risk factors demonstrated significantly greater right cIMT (0.681 ± 0.186 mm vs. 0.576 ± 0.144 mm, p < 0.001), left cIMT (0.711 ± 0.193 mm vs. 0.587 ± 0.143 mm, p < 0.001), and EFT (5.45 ± 2.30 mm vs. 4.24 ± 1.85 mm, p < 0.001) than controls. Hypertension, diabetes mellitus, and dyslipidaemia were each significantly associated with increased cIMT and EFT (all p < 0.001). The prevalence of abnormal cIMT increased from 2.2% in participants younger than 40 years to 28.0% in those older than 60 years ( p < 0.001). Progressively greater cIMT and EFT were observed with increasing cardiovascular risk-factor burden (both p < 0.001). Mean left cIMT was modestly but significantly greater than mean right cIMT (mean paired difference 0.026 mm, p < 0.001). Conclusions Asymptomatic adults with cardiovascular risk factors demonstrated significantly greater carotid intima-media thickness and epicardial fat thickness than those without risk factors. Increasing age and cumulative cardiovascular risk-factor burden were associated with progressive increases in both imaging markers. These findings support the use of cIMT and EFT as complementary non-invasive imaging markers that may improve cardiovascular risk stratification alongside conventional risk assessment.